2017
DOI: 10.1080/19440049.2016.1274431
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of food colour regulations in the EU and the US: a review of current provisions

Abstract: This review describes the European Union and the US regulations applicable to food colours. Despite the different regulatory frameworks, the overall approach is similar, based on wellestablished risk-assessment procedures and risk-management measures. However, differences impacting free movement of goods can be found in the details and implementation of regulations. Using additives approved only in the US or in the EU implies that producers aiming to export need to adjust their product composition to the expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…[29,30] Several carotenoids, including β-carotene and lycopene, are approved as food colorants. [31,32] Additionally, carotenoids are consumed in the form of nutritional supplements to increase their intake and to ensure an intake of those that are not usually present in common foods. [18]…”
Section: Dietary Sources Of Carotenoidsmentioning
confidence: 99%
“…[29,30] Several carotenoids, including β-carotene and lycopene, are approved as food colorants. [31,32] Additionally, carotenoids are consumed in the form of nutritional supplements to increase their intake and to ensure an intake of those that are not usually present in common foods. [18]…”
Section: Dietary Sources Of Carotenoidsmentioning
confidence: 99%
“…Fast Green FCF (FD&C Green No. 3, E143) is a FDA-approved triphenylmethane dye, while its usage as a food dye is prohibited in the EU [168]. When administered orally 200 mg of this dye to rats, the dye was excreted unchanged in the faeces and no dye was found in the urine [169].…”
Section: Diet Coloringmentioning
confidence: 99%
“…Testings in mice showed that the feeding of diets containing 3% Citurs Red 2 caused increased morbidity and mortality in both sexes [183]. Based on a number of similar reports suggesting that Citrus Red 2 has carcinogenic effects, the FDA approved this dye only for limited applications such as coloring the peel of oranges, while in the EU it is not permitted at all [168]. However, there it was recommended that this dye should not be used as a food additive [184].…”
Section: Diet Coloringmentioning
confidence: 99%
“…Almost all of them are not harmless and have varying degrees of toxicity associated with allergic, carcinogenic, and mutagenic effects. Maximum permitted levels of food dyes are steadily decreasing and now have reached 0.01 g of a dye per 100 g of a foodstuff [2]. erefore, their content in food products is strictly regulated and requires permanent monitoring.…”
Section: Introductionmentioning
confidence: 99%